A review of creative writing workshop pedagogy in educational research: methodological challenges and affordances. Issue 4 (1st October 2016) - Howe, Lori
ABSTRACT: This methodololgically focused review of the literature on creative writing workshop pedagogy explores the challenges and affordances of formal educational research, both qualitative and quantitative, in an area which continues to be dominated by lay research. Each of three qualitative studies, as well as one quantitative report, is examined for insights into best practices of data collection, analysis, and presentation. The purpose of this review of the literature is to offer implications for future research that may serve to bridge the gap between informal qualitative research and policy-makers, as lay research has historically had a limited impact on administration and policy regarding writing pedagogy. Possible avenues of research, as well as transferability of studies across myriad writing populations, both at-risk and mainstream, are considered.